2011
DOI: 10.1021/jf1043585
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of 3-Mercaptohexanol, Hydrogen Sulfide, and Methyl Mercaptan during Bottle Storage of Sauvignon blanc Wines. Effect of Glutathione, Copper, Oxygen Exposure, and Closure-Derived Oxygen

Abstract: The effects of wine composition and postbottling oxygen exposure on 3-mercaptohexanol (3-MH), hydrogen sulfide (H2S), and methyl mercaptan (MeSH) were investigated. A Sauvignon blanc wine with initial copper concentration of 0.1 mg/L was treated with copper sulfate and/or glutathione (GSH) prior to bottling to give final concentrations of 0.3 and 20 mg/L, respectively. The wines were bottled with a synthetic closure previously stored in either ambient air or nitrogen to study the effect of the oxygen normally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
193
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(204 citation statements)
references
References 29 publications
4
193
1
4
Order By: Relevance
“…Very few such studies on Sauvignon blanc wine have actually included precise oxygen measurements (Brajkovich et al, 2005;Lopes et al, 2009;Ugliano et al, 2011), thus still making it difficult to define how much oxygen would be beneficial for wine during bottle ageing. The type (variety and composition) and style (winemaking practices such as wood contact) of the wine are also expected to play a crucial role in the amount of oxygen required to achieve the ideal wine.…”
Section: Sauvignon Blanc Ageing and Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few such studies on Sauvignon blanc wine have actually included precise oxygen measurements (Brajkovich et al, 2005;Lopes et al, 2009;Ugliano et al, 2011), thus still making it difficult to define how much oxygen would be beneficial for wine during bottle ageing. The type (variety and composition) and style (winemaking practices such as wood contact) of the wine are also expected to play a crucial role in the amount of oxygen required to achieve the ideal wine.…”
Section: Sauvignon Blanc Ageing and Oxidationmentioning
confidence: 99%
“…However, GSH has also been shown to induce the production of H 2 S during wine ageing under lowoxygen conditions (Ugliano et al, 2011). Glutathione has been linked to the aroma potential of Sauvignon blanc grapes due to the identification of glutathionylated precursors for 3MH and 4MMP (Peyrot des Ganchos et al, 2002).…”
Section: The Role Of Antioxidantsmentioning
confidence: 99%
“…It was shown that lower ratios yielded lighter musts [4]. In contrast to the advantages of GSH, other researchers found that GSH can foster the formation of H 2 S and other sulfide off-flavours during fermentation [5]. Besides the proposed protective effect against chemical oxidation resulting in the glutathione disulfide (GSSG) [6] the protective effects against enzymatic oxidation during grape processing with subsequent formation of the Grape Reaction Products (GRP1 and GRP2) are reported [7].…”
Section: Introductionmentioning
confidence: 99%
“…El contenido de glutatión después de la fermentación puede depender de la cepa de a e-mail: jmartinezg@larioja.org levadura utilizada [7], aunque las diferencias observadas en algunos trabajos fueron insignificantes [10]. Durante el proceso de conservación del vino, la concentración de glutatión generalmente disminuye, pudiendo verse afectada de forma notable por la exposición al oxígeno durante el embotellado [11].…”
Section: Introductionunclassified
“…El contenido de glutatión después de la fermentación puede depender de la cepa de a e-mail: jmartinezg@larioja.org levadura utilizada [7], aunque las diferencias observadas en algunos trabajos fueron insignificantes [10]. Durante el proceso de conservación del vino, la concentración de glutatión generalmente disminuye, pudiendo verse afectada de forma notable por la exposición al oxígeno durante el embotellado [11].En los mostos, el glutatión juega un papel crucial limitando los procesos oxidativos de tipo enzimático. Después del prensado, las polifenoloxidasas inician las reacciones de oxidación de losácidos hidroxicinámicos y dan lugar a la formación de las correspondientes o-quinonas.…”
unclassified